Development of a Super Hybrid Duck Cultivation and Breeding Business Using Energy Efficient Hatching Machines in Blitar Regency - Azis, Rosidi; Novie Ary Priyanti; Sri Wahyuni; Raditya Pratama; Muhammad Rizza Pahlevi; Praptop Yuliadi (⁠International Journal of Asia Pacific Community Service, 2024)
The development of the super hybrid duck cultivation and breeding business in Blitar Regency is a strategic effort to increase the productivity and economy of local breeders. The use of energy-efficient hatching machines in developing super hybrid duck cultivation and breeding businesses in Blitar Regency is an innovative step in the livestock industry. This technology aims to increase efficiency, productivity and sustainability in the duck egg hatching process. The aim is to identify potential, challenges and solutions in developing a super hybrid duck cultivation and breeding business in the region. The research methods used were field surveys, interviews and data analysis. The results of this program show that Blitar Regency has considerable potential to develop a super hybrid duck cultivation business, but is still faced with a number of challenges such as lack of technical knowledge, inadequate infrastructure, and limited market access. Adoption of technology in developing and breeding super hybrid ducks through the use of machines, namely hatching machines designed to be energy efficient, including energy efficiency, reduced operational costs, increased productivity and quality of duck seeds. The implications of adoption of technology can reduce the environmental impacts and improve the economics of adopting this technology, as well as the challenges and opportunities associated. It is hoped that the various solutions proposed, including technical training and infrastructure improvements, can serve as a guide for all groups, including breeders, government and related stakeholders, in supporting the development of super hybrid duck cultivation and breeding businesses in Blitar Regency.